THE DISTRIBUTION OF CR BETWEEN BASALTIC MELT AND CHROMIAN SPINEL AS AN OXYGEN GEOBAROMETER - Poustovetov A.A.; Roeder P.L. (My University, 2001)
A thermodynamic model of Cr distribution between chromian spinel and basaltic melt has been developed using the Sack & Ghiorso (1991) thermodynamic model for chromian spinel and an equation analogous to that of Sack er nl. (1980) to calculate the Cr oxidation state in the melt. The model has been calibrated using published experimental data on the composition of coexisting chromian spinel and basaltic melt. The model can be used either to calculate the oxygen fugacity, f(O-2), of magmas saturated with chromian spinel, to predict the Cr content of the melt, or to calculate the oxidation state of Cr in the melt. The f(O-2) values calculated for a set of natural lavas (primitive MORB and a Hawaiian pumice) using the method show good agreement with f(O-2) values calculated from measured values of Fe3+/Fe2+ in the melt. An EXCEL spreadsheet for calculating log f(O-2) using composition of glass and chromian spinel is available from the authors upon request.